Zwodnicza szczerość(?) Jana Jakuba Rousseau czyli narracja jako kreacja i doświadczanie świata - Małgorzata Dagiel (Problemy Wczesnej Edukacji)
Literature remains somehow suspended between fiction and the truth, between pretending and authenticity. Each type of narration is, at the same time, a story and a creation, constructing the world portrayed on the experience of the speaker, taking into account the addressee, requirements of the genre selected and a set of ready-made schemas. The article analyses selected autobiographical works by J.J. Rousseau as a form of literary creation, as texts of culture that are rich in meaning, as the meeting place for the speaker, the text and the reader. It presents the attitude of the author/narrator towards the presented reality and the interesting process of its subjectivization, interpretation and evaluation.